Producing Indonesia the state of the field of Indonesian studies - Tagliacozzo, Eric (Cornell Modern Indonesia Project, 2014)
The twenty-six scholars contributing to this volume have helped shape the field of Indonesian studies over the last three decades. They represent a broad geographic background-Indonesia, the Netherlands, the United Kingdom, Australia, the United States, Canada-and have studied in a wide array of key disciplines-anthropology, history, linguistics and literature, government and politics, art history, and ethnomusicology. Together they reflect on the "arc of our field," the development of Indonesian studies over recent tumultuous decades. They consider what has been achieved and what still needs to be accomplished as they interpret the groundbreaking works of their predecessors and colleagues. This volume is the product of a lively conference sponsored by Cornell University, with contributions revised following those interactions. Not everyone sees the development of Indonesian studies in the same way. Yet one senses-and this collection confirms-that disagreements among its practitioners have fostered a vibrant, resilient intellectual community. Contributors discuss photography and the creation of identity, the power of ethnic pop music, cross-border influences on Indonesian contemporary art, violence in the margins, and the shadows inherent in Indonesian literature. These various perspectives illuminate a diverse nation in flux and provide direction for its future exploration